Dampak Pembelajaran Online Selama Pandemi Covid- 19 - Maulana, Mhd Irgi; Nasition, Nasition; Hasibuan, Leni Hermita; Hananiyah, Annisa; Nurhasanah, Sania; Nasution, Inom (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to identify or find out about how to apply online learning as a result of the Covid-19 that hit, so that the teaching and learning process is carried out from their respective homes. all data on very relevant matters from various available sources, namely through interviews and several references from several journals that can be picked up. The criteria for the sources chosen were discussions about the impact of the COVID-19 pandemic and online learning in elementary schools. From the sources obtained, the most relevant are then selected. The results in the study indicate that the impact of the COVID-19 pandemic on the application of online learning in elementary schools can be implemented quite well. This can be seen from the results of the data obtained showing that the impact of the COVID-19 pandemic on the application of online learning in elementary schools can be carried out quite well if there is collaboration between teachers, students and parents while studying at home.